2019
DOI: 10.3126/forestry.v16i0.28361
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Plant's Essential Oils against Post Harvest Fungal Disease of Apple Fruit

Abstract: Bioactive natural compounds are developed as alternatives to synthetic fungicides for the control of rot diseases of apple fruit. The antifungal activity of essential oils exudes from five plants, namely, Cinnamomum tamala, Lantana camara, Ageratina adenophora, Citrus limetta and Eucalyptus citriodora were evaluated in vitro against Colletotrichum gloeosporioides, Fusarium oxysporum and Alternaria alternata causing postharvest rot disease in apple fruits. The pathogens were isolated from infected apple fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Many essential oils (EOs) proved their effectiveness against grey mould and brown rot ( Monilinia species) on pome and stone fruit, strawberries, and table grapes [ 8 , 9 , 10 , 11 ]. On apples, various studies have reported the efficacy of EOs against blue mould ( Penicillium expansum ) [ 12 , 13 , 14 ], grey mould [ 8 , 12 , 15 , 16 ], and bitter rot ( Colletotrichum species) [ 17 , 18 ], as well as Alternaria and Fusarium rots [ 17 , 18 , 19 ]. Different researchers described the volatile organic compounds (VOCs) present in EOs, such as thymol, eugenol, p -cymene, and carvacrol, which show strong antifungal activity and could be used for grey mould control on fruit [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many essential oils (EOs) proved their effectiveness against grey mould and brown rot ( Monilinia species) on pome and stone fruit, strawberries, and table grapes [ 8 , 9 , 10 , 11 ]. On apples, various studies have reported the efficacy of EOs against blue mould ( Penicillium expansum ) [ 12 , 13 , 14 ], grey mould [ 8 , 12 , 15 , 16 ], and bitter rot ( Colletotrichum species) [ 17 , 18 ], as well as Alternaria and Fusarium rots [ 17 , 18 , 19 ]. Different researchers described the volatile organic compounds (VOCs) present in EOs, such as thymol, eugenol, p -cymene, and carvacrol, which show strong antifungal activity and could be used for grey mould control on fruit [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Fusarium oxysporum, a filamentous, hyaline, septate fungus belonging to the group of hyalohyphomycosis agents, is recognized as the cause of localized infections, such as keratitis and disseminated infections, with multisystemic involvement in immunocompromised patients (5). Similarly, these pathogens can affect ornamental and many garden crops (6) and are responsible for pre-and post-harvest diseases (7), generating significant economic losses (8).…”
mentioning
confidence: 99%